Peran Pers Dalam Menumbuhkan Nasionalisme - Riyanto, Buddy - (Transformasi, 2012)
AbstractFreedom of the press in Indonesia has now been secured by the statutory provisions. Freedom ofthe press is absolutely necessary for democratization that guarded the purpose of this nation.However, press freedom is not oriented to truth and loyalty to the public can be a threat to thefreedom of the press itself. In some ways the mass media or the press often have to adjust to theconditions in which they are included in the territory of a country. If the press and the nation areequally oriented to truth and public interests or citizens of the nation itself, then the press can besaid to have had the spirit of togetherness and nationality.Key Words: Freedom of The Press, Nationalism.